In-vitro Study for Cerenkov Luminescence Imaging Application in Hepatic Metastasectomy - Ciarrocchi, Esther; Saponaro, Sara; Bartoli, Francesco; Cataldi, Angela Gabriella; Vitali, Sara; Erba, Paola Anna; Belcari, Nicola (Frontiers in Physics, 2021)
Cerenkov luminescence imaging (CLI) has been recently proposed as a method to visualize surgical margins in the operating theater, immediately after resection, to allow refining surgery in a single procedure. Our group is preparing a pilot clinical study to evaluate the impact of CLI during hepatic metastasectomy, using 18F-FDG and 68Ga-DOTATOC. Currently, we are optimizing the clinical protocol in terms of patient inclusion criteria, activity to inject, maximum allowed delay for imaging, and radiation monitoring. This paper describes a preliminary study we have performed to define the clinical protocol. The study is composed of two branches: i) an in-vitro study to predict the typical signals and optical attenuation in the liver with 18F and 68Ga, ii) an analysis of clinical PET/CT data to determine typical values of relevant parameters, such as uptake and lesion dimension. The combined information by these two branches gives us an indication of the feasibility of CLI for margin assessment in liver metastasectomy. For 68Ga, we obtained detection limits ranging from 0.55 to 3.5 kBq/cc, to be compared with minimum and mean clinical uptakes of 1.6 and 7 kBq/cc, respectively. For 18F, the detection limits ranged from 12 to 145 kBq/cc, and the minimum and mean clinical uptakes were 5 and 11 kBq/cc, respectively. From these values, we expect CLI with 68Ga to be able to detect surgical margins in most patients, while with 18F the activities to inject for sufficient signal-to-noise ratio should be larger than standards, or the time delay between injection and imaging largely reduced. The results reported here can be useful also more in general, for studies dedicated to other CLI applications in the liver.